1993
DOI: 10.1016/0014-5793(93)81178-3
|View full text |Cite
|
Sign up to set email alerts
|

Conformational junctions between left‐handed DNA in (dA‐dT)16 and contiguous B‐DNA in a supercoiled plasmid contain chemically reactive bases

Abstract: Alternating adenine-thymine sequences in supercoiled DNA may undergo a transition to the left-handed Z-conformation in the presence of Ni2+ ions and high Na' concentrations [(1989) FEBS Lett. 243, 313-3171. In this work we have studied the junctions between B-and Z-conformations in a supercoiled plasmid containing a (dAdT),, insert, by means of chemical probing. We observed enhanced reactivity of bases at both ends of the alternating tract to chloro-and bromoacetaldehyde. The degree of chemical reactivity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Characterizing changes in supercoiling is therefore essential for understanding these processes in detail. Moreover, modulation of supercoiling accompanies conformational changes in duplex DNA such as cruciform extrusion [12, 24–28] and the formation of Z-DNA [12, 13, 2730], and is thus an important topological method for analyzing alternative DNA conformations.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing changes in supercoiling is therefore essential for understanding these processes in detail. Moreover, modulation of supercoiling accompanies conformational changes in duplex DNA such as cruciform extrusion [12, 24–28] and the formation of Z-DNA [12, 13, 2730], and is thus an important topological method for analyzing alternative DNA conformations.…”
Section: Introductionmentioning
confidence: 99%
“…pXGAT15 is a 3.8 kb plasmid that contains an (dA-dT) 15 tract (14,16). The polarity of the tract is the same as that in pAT32, but the context of the alternating tract is more similar to that found in pTA16 (Figure 3).…”
Section: Effect Of Sequence Context On the B-to-z Transition In (Da-dmentioning
confidence: 99%
“…Furthermore, we have previously found that (dA-dT) 16 block can become lefthanded in the presence of high NaCI concentrations and Ni2+ ions if the structure is stabilised by negative supercoiling (13). Recently we have probed putative B-Z junctions adjoining the (dA-dT) 16 block using chemical agents, and found reactive bases at both boundaries between B-DNA and the left-handed segment in the supercoiled plasmid (14).…”
Section: Introductionmentioning
confidence: 97%
“…The longest alternating PyPu sequence in pSM1 DNA is 20 base-pairs long and is centered at nucleotide 2390. This sequence contains a stretch of alternating (dT-dA) 3 •(dT-dA) 3 base-pairs and is not surrounded by a region of high G + C content, hence is not likely to form a Z-DNA structure at any reasonably attainable level of supercoiling (McLean et al, 1986;Nejedly et al, 1993).…”
Section: Characteristic Features Of the Secondary Structurementioning
confidence: 99%